Evaluation of a continuously active disinfectant for decontamination of portable medical equipment. (26th March 2022) - Redmond, Sarah N.; Cadnum, Jennifer L.; Silva, Sandra Y.; Pearlmutter, Basya S.; Jencson, Annette L.; Alhmidi, Heba; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: A single spray application of a continuously active disinfectant on portable equipment resulted in significant reductions in aerobic colony counts over 7 days and in recovery of Staphylococcus aureus and enterococci: 3 of 93 cultures (3%) versus 11 of 97 (11%) and 20 of 97 (21%) in quaternary ammonium disinfectant and untreated control groups, respectively.